MASTER-NAADP: a membrane permeable precursor of the Ca2+ mobilizing second messenger NAADP - Krukenberg, Sarah; Möckl, Franziska; Weiß, Mariella; Dekiert, Patrick; Hofmann, Melanie; Gerlach, Fynn; Winterberg, Kai J.; Kovacevic, Dejan; Khansahib, Imrankhan; Troost, Berit; Hinrichs, Macarena; Granato, Viviana; et al. (Nature Communications, 2024)
Upon stimulation of membrane receptors, nicotinic acid adenine dinucleotide phosphate (NAADP) is formed as second messenger within seconds and evokes Ca2+ signaling in many different cell types. Here, to directly stimulate NAADP signaling, MASTER-NAADP, a Membrane permeAble, STabilized, bio-rEversibly pRotected precursor of NAADP is synthesized and release of its active NAADP mimetic, benzoic acid C-nucleoside, 2’-phospho-3’F-adenosine-diphosphate, by esterase digestion is confirmed. In the presence of NAADP receptor HN1L/JPT2 (hematological and neurological expressed 1-like protein, HN1L, also known as Jupiter microtubule-associated homolog 2, JPT2), this active NAADP mimetic releases Ca2+ and increases the open probability of type 1 ryanodine receptor. When added to intact cells, MASTER-NAADP initially evokes single local Ca2+ signals of low amplitude. Subsequently, also global Ca2+ signaling is observed in T cells, natural killer cells, and Neuro2A cells. In contrast, control compound MASTER-NADP does not stimulate Ca2+ signaling. Likewise, in cells devoid of HN1L/JPT2, MASTER-NAADP does not affect Ca2+ signaling, confirming that the product released from MASTER-NAADP is a bona fide NAADP mimetic.
Im Titel ist 2+ hochgestellt
Der Vorname von Hub, Tobias ist in der Vorlage fälschlich als Tobis genannt
Gesehen am 07.05.2025